Students’ Conceptual Understanding through Implementation of LiveWire in Basic Electronics Virtual Experiment - Muh. Makhrus; Wahyudi Wahyudi; Muhammad Zuhdi (Postgraduate, University of Mataram, 2021)
As a result of Covid-19, the learning system has changed towards online learning. Practicum activities encountered obstacles and had to be replaced by virtual experiments. This study aims to see the role of virtual experiments during online learning in basic electronics courses and to describe students' conceptual understanding. The subject in this study amounted to 56 students. The research data collection instrument used a conceptual understanding test. Data were analyzed by descriptive statistics This virtual experiment using the LiveWire application. The results showed that virtual experiments carried out during online learning were able to help students' practicum activities and most students had a high category understanding of concepts after learning. This shows that virtual experiments with LiveWire can be used as an alternative to assist practicum activities when doing online learning.